The Effect of Consumer Perceptions and Innovation Adoption on Their Intentions to Purchase Online - Anisah; Indrayani, Emmy; Mukodim, Didin (Yayasan Ilomata, 2024)
Technological changes affect various aspects of human life and daily activities. Technological advances can make the intensity of human perception comprehensive; the benefits, risks, and convenience felt when shopping online will certainly influence intentions. This research aims to analyse perceived benefits, perceived risks, perceived ease of use, and consumer innovation adoption on online shopping intentions simultaneously and partially. The population in this study consisted of people who had or were currently shopping online. The sample for this research consisted of 388 respondents. The sampling technique is non-probability sampling using the purposive sampling method. Primary data by distributing questionnaires to potential consumer respondents. The analysis techniques used are instrument tests, multiple linear regression, the F test, the t test, and the coefficient of determination. The research results show that perceived benefits, perceived risks, perceived ease of use, and consumer innovation adoption simultaneously and partially influence online shopping intentions. Consumers are expected to know their rights and obligations in terms of protection and do not need to hesitate to report the risks they receive when shopping online.